Diagnosis and Management of Cushing's Syndrome During Pregnancy: Two Cases Report and Literature Review - Jingjing Huang; Zhiyu Deng; Guohua Li; Deshui Zhao (Clinical Case Reports)
ABSTRACT Cushing's syndrome (CS) during pregnancy is a rare condition, with only a few reported cases in the literature. Diagnosis is often difficult due to physiological changes during pregnancy. Careful clinical observation during pregnancy and after delivery is necessary to initiate appropriate treatment.